Road safety inspection and road assessment programme - Várhelyi, András (Traffic Safety Data : Sources, analysis and applications, 2025)
Road Safety Inspection (RSI) and Road Assessment Programme (RAP) are specific tools in the framework of Road Infrastructure Safety Management. Other tools are Black-spot Management, Network Safety Management, Road Safety Impact Assessment and Road Safety Audit. This chapter is devoted to RSI and RAP.